Prognostic significance of venous invasion and maximum standardized uptake value of 18F-FDG PET/CT in surgically resected T1N0 esophageal squamous cell carcinoma. Issue 2 (February 2017) - Jeon, J.H.; Lee, J.M.; Moon, D.H.; Yang, H.C.; Kim, M.S.; Lee, G.-K.; Zo, J.I.
Abstract: Background: The purpose of this study was to analyze the risk factors of recurrence in patients with early stage esophageal squamous cell carcinoma (ESCC). Methods: We retrospectively analyzed the medical records of 190 patients with confirmed T1N0M0 ESCC after curative esophagectomy. The following potential prognostic factors for recurrence were investigated: age, sex, pathologic T category, tumor location, differentiation grade, tumor size, venous invasion, angiolymphatic invasion, perineural invasion and the maximum standardized uptake value (SUVmax) of the primary tumor. Results: There were 174 male and 16 female patients with a median age of 66.0 years (range, 42.0–79.0 years). The pathologic status of the surgically resected ESCCs was T1a in 93 patients (48.9%) and T1b in 97 patients (51.1%). The median number of dissected lymph nodes was 35 (range, 10 to 86), and all lymph nodes were negative for tumors. The multivariate analysis showed presence of venous invasion [HR (hazard ratio), 11.433; P < 0.001) and SUVmax ≥ 3.2 (HR, 2.830; P = 0.011) as independent risk factors for recurrence. The 5-year recurrence-free survival (RFS) was 25.0% for patients with venous invasion and 78.9% for those without ( P < 0.001). The 5-year RFS was 67.1% for patients with an SUVmax ≥3.2 and 81.5% for those with an SUVmax <3.2 ( P = 0.003). Conclusions: Venous invasion and high SUVmax could be important prognostic factors coupled with the TNM staging system, in patients with early stage ESCC.